Assessment of In vitro Antidiabetic Activity in Selected Species of Berberis L. - Goswami, Trishna; Joshi, Giri Prasad; Pant, Deepak Raj (Journal of Nepal Biotechnology Association, 2026)
Species of Berberis, especially their roots, have long been used in traditional medicine to manage hyperglycemia. However, only a few species are commonly used for this purpose. Although more than 20 species of Berberis are found in Nepal, only two species, namely B. aristata and B. asiatica, are widely utilized in traditional medicinal practices. The present study aims to evaluate the therapeutic potential of five Berberis species (B. concinna, B. everestiana, B. hamiltoniana, B. insignis, and B. jaeschkeana) by assessing their total phenolic content, total flavonoid content, and in vitro α-glucosidase inhibitory activity. On the basis of parameters evaluated, B. hamiltoniana emerged as the most promising species exhibiting the highest total phenolic content (66.97 ± 2.56 mg GAE/g) and the lowest half maximal inhibitory concentration (IC50 10.64 μg/ml) against α-glucosidase. Its inhibitory activity surpassed that of acarbose, the standard drug commonly used in the management of hyperglycemia.